10-3n=12

Simple and best practice solution for 10-3n=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3n=12 equation:


Simplifying
10 + -3n = 12

Solving
10 + -3n = 12

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -3n = 12 + -10

Combine like terms: 10 + -10 = 0
0 + -3n = 12 + -10
-3n = 12 + -10

Combine like terms: 12 + -10 = 2
-3n = 2

Divide each side by '-3'.
n = -0.6666666667

Simplifying
n = -0.6666666667

See similar equations:

| V-5/8=-1/4 | | 3n-10=12 | | f(x)=x^6/(2lnx) | | 32a^3-24a^2+36a=0 | | 1/x=-27/28 | | 80+13x=145 | | z/5-6=10/3 | | -7(v+2)=-4v-44 | | 3.53x+100=12.4609+10x | | -8h-8(2-4h)= | | 6(2n+3)=6(4n+5)+5 | | 7g-2(3g+1)-9= | | -w/-20=-2.5 | | 2x+16=3x^2 | | F(4)=-4+1 | | 3xy-y=2+5x | | -9/7x=3/4 | | 2.5(3p+5)=5p+12.5 | | 6(5u+1)-3(4u-12)= | | 4(2n+1)=7(3n+8)+2 | | 2b+b=450 | | 10z/7-3=3z/2 | | F(0)=0+1 | | 6=5/8t-9 | | 4/5=9/2-3a/10 | | 1+8(19-3m)= | | F(-1)=1+1 | | .33(9-2x)=x+1 | | 36w+10+7w= | | 3(2-2)/2=-z | | w^4/5-16=0 | | 9-3(4-3r)+12r= |

Equations solver categories